Fashion : a history from the 18th to the 20th century : the collection of the Kyoto Costume Institute - Fukai, Akiko; Iwagami, Miki; Suoh, Tamami; Kyōto Fukushoku Bunka Kenkyū Zaidan (Köln : Taschen, 2002)
Avant-propos - XVIII° siècle, XIX° siècle, XX° siècle
Bibliografische referenties ; glossarium ; index
Museumcatalogus
Keywords: Fashion -- History -- 18th century -- Pictorial works; Fashion -- History -- 19th century -- Pictorial works; Fashion -- History -- 20th century -- Pictorial works